Rancang Bangun dan Analisis Mesin Pemimpil Jagung dengan Daya Motor Listrik 1 HP - Nailul Ulum, Muhammad Showi; Tantoko, Ajid; Wahyudi, Anis Fuad; Saputra, Efendi Rika (Politeknik Negeri Semarang, 2023)
Sheller postharvest handling is a way to get attention. Corn sheller machine with 1 hp electrical machines power is designed to make it easier to scale postharvest handling household. This machine has using the final round 280 rpm. By the time the electric machines is turned on, the first pulley mounted on the motor will rotate and move the belt pulleys 2 then connected and will move the pulleys 3 and then move the disk sheller who will perform sheler inserted through the sleeve corn sheller and corn seeds will come out through the outlet of the seed corn and cob will exit through the outlet cob. This machine is operated semi-automatically by turning on the switch in the ON position and turn off the switch in the OFF position, and this machine can function properly as expected.Keyword : disk sheller , electrical machines, shealer corn machines,